ANALISIS STRATEGI DENGAN METODE SWOT DAN QSPM : STUDI KASUS PADA GRIYA COKELAT NGLANGGERAN - Muharromah, Restu Siwi; Kismantoroadji, Teguh (Jurnal AGRISEP, 2024)
The purpose of the study is to (1) examine the strategies that currently applied to Griya Cokelat Nglanggeran (2) to design the strategic decisions that can be applied for the development of Griya Cokelat Nglanggeran. This research is a quantitative research with the method of implementation by using descriptive research, taking saturated sampling (census sampling) involving all 13 available respondents. Techniques of collecting data used are interviews, observation, documentation and literature study. Data analysis techniques will be tested with IFE (Internal Factor Evaluation) matrix and EFE (External Factor Evaluation) matrix, IE (Internal-External) matrix, SWOT (Strength, Weakness, Opportunity, Threat) matrix and QSPM (Quantitative Strategic Planning Matrix) to decide the best strategic that can be applied. Based on the data in the processed matrix, the study draws key conclusions that (1) it highlights that the current strategies in Griya Cokelat Nglanggeran, particularly in production and marketing are limited. (2) The strategy applied based on the calculation on the SWOT matrix is the WO (Weakness-Opportunity) Strategy and the right strategy decision to be applied based on the QSPM matrix is a market development strategy based on the QSPM matrix analysis results. Overall, these findings provide valuable insights for the enhancement of Griya Cokelat Nglanggeran's business strategies.